The Response of Bank of Indonesia's Interest Rates to the Prices of World Crude Oil and Foreign Interest Rates - Adam, Pasrun (International Journal of Energy Economics and Policy, 2016)
This research aimed to investigate the response of interest rates set by Bank of Indonesia to the prices of world crude oil and foreign interest rates. It analyzed monthly data which spanned from July 2005 to October 2015. The tool of analysis used was the difference equation model. Result of the test showed that there was a positive response of the interest rate determined by Bank of Indonesia to the price of world crude oil and foreign interest rates. The interest rates maintained by Bank of Indonesia increased (decreased) by 0.135% in response to each 1% increase (decrease) in the price of world crude oil. The interest rates also increased (decreased) by 0.081% in response to each 1% increase (decrease) in foreign interest rates. Keywords: World crude oil price, foreign interest rates, domestic interest rates, difference equation model JEL Classications: C540, E430